The Effectiveness of Popular Songs for Developing Listening Skills of Form One Intermediate Level Students - Md. Salleh, Nora (1998)
This study aims at ascertaining the Form One listening skill through the use of popular songs as well as provide variety in classroom teaching and learning. This study also tries to determine students' perception of the use of popular songs in the classroom. The result shows that more than 80% of the respondents in Sekolah Menengah Kebangsaan Taman Sri Muda Shah Alam agree that popular songs can aid in developing listening skills among students.